A Paratesticular Angiolipoma: A Case Report of a Rare Benign Scrotal Mass and Review of Literature. (20th June 2019) - Nouioui, Mohamed Ali; Taktak, Tarek; Mokadem, Seif; Gargouri, Faten; Mediouni, Houssem; Khiari, Ramzi; Ghozzi, Samir
Abstract : We report a rare case of paratesticular angiolipoma in a young male. The patient is a 21-year-old male who presented with a palpable firm right intrascrotal mass of 21 mm. Ultrasound findings demonstrated that it is a solid mass. Under the diagnosis of an intrascrotal solid mass, a right inguinal radical orchiectomy was performed. Histopathological examination concluded to a paratesticular angiolipoma. Angiolipoma is a rare benign form of paratesticular tumour and its diagnosis is based on histological findings of the surgical specimen with no recurrence risk. This mesenchymal tumour should be distinguished from liposarcoma, which has malignant or aggressive clinical course.